Rheumatic fever and rheumatic heart disease: Where are we now in South Africa? - Engel, Mark E.; Zühlke, Liesl; Robertson, Kate (SA Heart Journal, 2017)
South Africa continues to face unacceptably high rates of rheumatic fever (RF) and rheumatic heart disease (RHD), despite readily available and inexpensive preventive measures. However, in the past several years, key players in South Africa’s healthcare and political realms in addition to key players from many African nations have come together to acknowledge the persistent health burden attributable to RF/RHD and have agreed to a pledge of action to reduce it. The plan of action is a comprehensive RF/RHD prevention and treatment programme known as ASAP. The ASAP programme targets efforts to raise Awareness, establish Surveillance systems, Advocate for increased resources for treatment, and to promote Prevention strategies. South Africa currently has a demonstration site where activities in all of these key areas are currently underway. Efforts in the area of surveillance include a RHD prevalence study that aims to screen 4 000 school-aged children through the use of a mobile echo-surveillance unit. In addition to local efforts, South Africa will join an international initiative to create a global RHD registry that will aid in all aspects of prevention and treatment to further reduce the burden of disease attributable to RF/RHD.